core trisaccharide of an N-linked glycoprotein intrinsically accelerates folding and enhances stability - Hanson, Sarah R; Culyba, Elizabeth K; Hsu, Tsui-Ling; Wong, Chi-Huey; Kelly, Jeffery W; Powers, Evan T (Proceedings of the National Academy of Sciences - PNAS, 2009)
The folding energetics of the mono-N-glycosylated adhesion domain of the human immune cell receptor cluster of differentiation 2 (hCD2ad) were studied systematically to understand the influence of the N-glycan on the folding energy landscape. Fully elaborated N-glycan structures accelerate folding by 4-fold and stabilize the β-sandwich structure by 3.1 kcal/mol, relative to the nonglycosylated protein. The N-glycan's first saccharide unit accounts for the entire acceleration of folding and for 2/3 of the native state stabilization. The remaining third of the stabilization is derived from the next 2 saccharide units. Thus, the conserved N-linked triose core, ManGlcNAc₂, improves both the kinetics and the thermodynamics of protein folding. The native state stabilization and decreased activation barrier for folding conferred by N-glycosylation provide a powerful and potentially general mechanism for enhancing folding in the secretory pathway.